Thought, Sex, and Language The Sapir-Whorf Hypothesis as Implicit Ideology and Rhetorical Strategy in the American Women's Movement - Schneider, Michael J.; Foss, Karen A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The women's movement has made the issue of language usage an important part of its ideology and an even more important part of its rhetoric. Generally, the position assumed is that English is biased in favor of the male in terms of both syntax and semantics. Much of the work which women have published on this issue reflects a close adherence to the Sapir-Whorf hypothesis, which asserts that language determines thought. Recent limitations which have been placed on this hypothesis have important implications for the rhetoric of the women's movement. Since linguistic bias is actually a symptom rather than a cause of social bias, feminists risk a loss of credibility by asserting a causative relationship between thought and language. Analysis of linguistic biases can, however, help to uncover the nature of underlying social biases, help to keep feminist issues before the public, provide a concrete index of progress toward eliminating social biases, and serve to boost women's morale and to improve their self-concepts. (KS)
ERIC Note: An earlier version of this paper was presented at the Fifth Biennial International Colloquium on Verbal Communication (University of South Florida, Tampa, July 26, 1976).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bias; Cognitive Processes; Feminism; Linguistic Theory; Linguistics; Sex Discrimination; Sexism in Language; Social Attitudes; Social Change; Social Values; Whorfian Hypothesis; Reports, Research